Optimal Cerebral Perfusion Pressure Guided by Brain Oxygen Pressure Measurement - Kovacs, Matyas; Peluso, Lorenzo; Njimi, Hassane; De Witte, Olivier; Gouvêa Bogossian, Elisa; Quispe Cornejo, Armin; Creteur, Jacques; Schuind, Sophie; Taccone, Fabio Silvio (Frontiers in Neurology, 2021)
Background: Although increasing cerebral perfusion pressure (CPP) is commonly accepted to improve brain tissue oxygen pressure (PbtO2), it remains unclear whether recommended CPP targets (i.e. > 60 mmHg) would result in adequate brain oxygenation in brain injured patients. The aim of this study was to identify the target of CPP associated with normal brain oxygenation. Methods: Prospectively collected data including patients suffering from acute brain injury and monitored with PbtO2, in whom daily CPP challenge using vasopressors was performed. Initial CPP targets were >60 mmHg; norepinephrine infusion was modified to have an increase in CPP of at least 10 mmHg at two different steps above the baseline values. Whenever possible, the same CPP challenge was performed for the following days, for a maximum of 5 days. CPP “responders” were patients with a relative increase in PbtO2 from baseline values >20%. Results: A total of 53 patients were included. On the first day of assessment, CPP was progressively increased from 73 [70-76] to 83 [80-86] and 92 [90-96] mmHg, which resulted into a significant PbtO2 increase (from 20 [17-23] mmHg to 22 [20-24] mmHg and 24 [22-26] mmHg, respectively; p<0.001). Median CPP value corresponding to PbtO2 values > 20 mmHg was 79 [74-87] mmHg, with 2 (4%) patients who never achieved such target. Similar results of CPP targets were observed the following days. A total of 25 (47%) were PbtO2 responders during the CPP challenge on day 1, in particular if low PbtO2 was observed at baseline. Conclusions: PbtO2 monitoring can be an effective way to individualize CPP values to avoid tissue hypoxia. Low PbtO2 values at baseline can identify the responders to the CPP challenge.